Liturgia w Polsce w XV wieku .......... 37 - Pałęcki, Waldemar Jan (Graduał wawelski (Kraków, AiBKKK, Ms 45): Studium przypadku, 2025)
LITURGY IN POLAND IN THE 15TH CENTURYThe liturgy in the 15th century was an important stage in the history of the Church in Poland. It was a time when, on the one hand, there was an attempt to unify the liturgy celebrated within the dioceses or ecclesiastical provinces, and, on the other hand, there was a desire to preserve one’s own liturgical traditions. With the use of the historical-critical method, and on the basis of representative liturgical books and liturgical-pastoral treatises of that time, the celebration of the liturgy in 15th-century Poland is shown, which was the purpose of this study. The conducted research allowed to show in a synthetic way the differences in the celebration of the Holy Mass in Poland in comparison with the Roman liturgical books of that time, to distinguish the use of certain liturgical paraments (e.g. the so-called szerzynka), and to present the particularity in the celebration of the other sacraments (e.g., the transition from baptism through immersion to baptism through the glade), and especially in the celebration of the sacrament of marriage. Liturgical drama, the renewed cult of Polish patron saints and an orderly catalogue of obligatory feasts played an important role during this time.